ANALISIS KEPUASAN KONSUMEN TERHADAP KOPI HALAL NETWORK INTERNATIONAL (HNI) PRODUK PT. HPAI DI WONOGIRI, INDONESIA - Indra Setiawan; Risky Yuniar Rahmadieni; Sari Rejeki (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract: Research with quantitative descriptive methods was carried out on Coffe HNI products. The purpose of this study is to determine whether customer satisfaction from Coffe HNI products is influenced by price, product quality, and promotion. Customer satisfaction is important for a business if they don’t want to lose their customers. Coffe HNI is a coffe product that has been established since 2012 in Indonesia. The population in this study is Coffe HNI customer who live and have activities in Wonokarto Kelurahan, Wonogiri. Samples taken as many as 100 respondents using the Random Sampling method through direct distribution to outlets in Wonokarto and through Google Form. Quantitative analysis technique with the analytical toolusedisPartialLeastSquare(PLS).Theresultsshowedthatthepriceandproduct quality variables were influential and significant for customer satisfaction. While promotion variables have no effect and are not significant for customer satisfaction. Keywords: Customer Satisfaction, Price, Product Quality, Service Quality, Promotion